An Analysis of Difficulties Faced by English Education Study Program Students Seventh Semester in The Field Experience Program in Teaching during Covid-19 Pandemic - Rani Oktaviani; Yanti Ismiyati; Khidayatul Munawwaroh (Universitas Batanghari Jambi, 2021)
The purpose of the research is to find out the difficulties of students seventh semester has difficult in teaching while following the practical field of experience program during Pandemic Covid-19. The research methodology of this study was a qualitative research design, and a phenomenology approach with technic data collection using purposive sampling. The total of respondent that allowed of this research is six students. The respondent are students at seventh semester in English education department that had been done the practical field of experience program during Pandemic Covid-19. The result of the research that a half of students seventh semester got difficulties in ability and stress when teaching in class. The student difficulties in teaching are teaching model, teaching material, time in teaching and stress in teaching means psychology students feel when did the practical field of experience. There were 4 of 6 students at seventh semester considered that time in teaching while did PPL program was very short and ineffective for explaining the material in class. Then, there were 3 of 6 students at seventh semester had felt afraid, shock, nervous or consume when taught at first time. The cause of the students’ difficulties in teaching while doing PPL program during Pandemic Covid-19 are the lack of students at seventh in discipline students at school while learning process, they depended used application that expensive in cost internet data, they felt disappointed cause not gave the best performance in English learning process in class that they had studied while in university.Keywords: The Field of Experience Program, Students Difficulties in Teaching.